Has monetary policy become less powerful? - Jean Boivin; Marc Giannoni (Federal Reserve Bank of New York, 2002)
Recent vector autoregression (VAR) studies have shown that monetary policy shocks have had a reduced effect on the economy since the beginning of the 1980s. This paper investigates the causes of this change. First, we estimate an identified VAR over the pre- and post-1980 periods, and corroborate the existing results suggesting a stronger systematic response of monetary policy to the economy in the later period. Second, we present and estimate a fully specified model that replicates well the dynamic response of output, inflation, and the federal funds rate to monetary policy shocks in both periods. Using the estimated structural model, we perform counterfactual experiments to quantify the relative importance of changes in monetary policy and changes in the private sector in explaining the reduced effect of monetary policy shocks. The main finding is that changes in the systematic elements of monetary policy are consistent with a more stabilizing monetary policy in the post-1980 period and largely account for the reduced effect of unexpected exogenous interest rate shocks. Consequently, there is little evidence that monetary policy has become less powerful.
Keywords: E52; E3; C32; 330; Transmission of monetary policy; Vector autoregression; Minimum distance estimation; Dynamic general equilibrium model; Habit-formation.; Geldpolitik; Schock; Transmissionsmechanismus; Wirkungsanalyse; USA